APLIKASI FUZZY c-MEANS CLUSTERINGUNTUK MENGELOMPOKKAN DATA GEMPABUMI DI PROVINSI BENGKULU - Nur Afandi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
This study aims to cluster earthquake events in Bengkulu Province and describe the characteristics of each group based on clustering results. The method used is Fuzzy c-Means Clustering. The clustering results show that although clustering is formed based on the location of latitude, longitude, and depth, the data is only clumped by depth. Based on the XB index and the Silhouette index the three best clustering sequences are clustering using 2 clusters, 5 clusters, 8 clusters.